miRNAs Can Affect Intestinal Epithelial Barrier in Inflammatory Bowel Disease - Xiao, Xiangjun; Mao, Xiangbing; Chen, Daiwen; Yu, Bing; He, Jun; Yan, Hui; Wang, Jianping (Frontiers in Immunology, 2022)
The most obvious pathological characterization of inflammatory bowel disease (IBD) is intestinal epithelium erosion and severe inflammation invasion. Micro-ribonucleic acids (miRNA or microRNA), single-stranded noncoding RNAs of ~22 nucleotide, have been considered as the potential therapeutic targets in the pathogenesis of IBD. Many previous studies have focused on the mechanisms that miRNAs regulate inflammation, immunity and microorganisms in IBD. The review highlights in detail the findings of miRNAs in intestinal epithelial barrier of IBD, and focuses on their gene targets, signaling pathways associated with IBD, and some potential therapies. It will be beneficial for elucidation of the interaction between miRNAs and intestinal epithelial barrier in IBD, and provide a theoretical reference for preventing and treating IBD in the future.